Isolation and characterization of quinine from Polygonatum verticillatum: A new marker approach to identify substitution and adulteration - Jaswinder Kaur Virk; Sanjiv Kumar; Ranjit Singh; Avinash C Tripathi; Shailendra K Saraf; Vikas Gupta; Parveen Bansal (Wolters Kluwer Medknow Publications, 2016)
Polygonatum verticillatum (Mahameda) is an important ingredient of Ashtawarga and Ayurvedic formulations. Nowadays, it comes under the category of endangered plants due to large scale and indiscriminate collection of wild material. To overcome the scarcity, substitutes of Mahameda are also commonly used in market. These additives are different from the authentic plant by Ayurvedic and pharmacological theory of drug action, thereby resulting in substitution/adulteration. Substitution is a critical issue in isolation and quantification of the therapeutically active ingredients that can be used as markers in the identification of substitution/adulteration. Methanolic extract of the rhizomes of P. verticillatum was subjected to preliminary phytochemical screening for the detection of phytoconstituents, followed by column chromatography for isolation of the marker. The column was first eluted with pure hexane, and polarity of the solvent was gradually increased. A total of 1180 fractions were collected and pooled on the basis of thin-layer chromatography profile. The single compound was isolated and confirmed by chemical test, melting point, spectral analysis, and comparison with literature. Phytochemical screening of the extract shows the presence of alkaloids, flavonoids, carbohydrates, terpenoids, and phenolics. A pure white crystalline powder was isolated by column chromatography which was characterized as (6-methoxyquinolin-4-yl-8-vinylquinuclidin-2-yl) methanol, i.e. Quinine. The isolated compound, Quinine, was identified as a novel compound in Mahameda as it has not been reported in the genus Polygonatum, till now. It can be used as a marker for the identification of substitution/adulteration and standardization of P. verticillatum.